Roles of tumor necrosis factor receptor associated factor 3 (TRAF3) and TRAF5 in immune cell functions - Hildebrand, Joanne M. (2011)
A large and diverse group of receptors utilizes the family of cytoplasmic signaling proteins known as tumor necrosis factor receptor (TNFR)-associated factors (TRAFs). In recent years, there has been a resurgence of interest and exploration of the roles played by TRAF3 and TRAF5 in cellular regulation, particularly in cells of the immune system, the cell types of focus in this review. This work has revealed that TRAF3 and TRAF5 can play diverse roles for different receptors even in the same cell type, as well as distinct roles in different cell types. Evidence indicates that TRAF3 and TRAF5 play important roles beyond the TNFR-superfamily (SF) and viral mimics of its members, mediating certain innate immune receptor and cytokine receptor signals, and most recently, signals delivered by the T-cell receptor (TCR) signaling complex. Additionally, much research has demonstrated the importance of TRAF3-mediated cellular regulation via its cytoplasmic interactions with additional signaling proteins. In particular, we discuss below evidence for the participation by TRAF3 in a number of the regulatory post-translational modifications involving ubiquitin that are important in various signaling pathways.